2019
DOI: 10.1111/zph.12634
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic burden of severe fever with thrombocytopenia syndrome in endemic areas of Anhui Province, eastern China

Abstract: Understanding the socioeconomic burden of severe fever with thrombocytopenia syndrome (SFTS) is important for making decisions on health resources allocation. This study aimed to assess the economic burden of patients with this syndrome in endemic areas of the Anhui Province in 2018. A total of 114 patients were recruited, and the median age was 63.5 years, 62 (54.4%) were female, 97 (85.1%) were farmers, 108 (94.7%) were survival patients, and 71 (62.3%) had a family monthly income less than $453.3. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Our previous study reported that the medical history of SFTS cases included one time of outpatient and two times of inpatients. 19 This study further demonstrated that fatal cases had shorter durations of hospitalization and clinical course than nonfatal cases. One of the reasons for this might be the rapid worsening of the clinical course in fatal cases, with most patients dying in the multi-organ dysfunction phase.…”
Section: Discussionmentioning
confidence: 52%
“…Our previous study reported that the medical history of SFTS cases included one time of outpatient and two times of inpatients. 19 This study further demonstrated that fatal cases had shorter durations of hospitalization and clinical course than nonfatal cases. One of the reasons for this might be the rapid worsening of the clinical course in fatal cases, with most patients dying in the multi-organ dysfunction phase.…”
Section: Discussionmentioning
confidence: 52%
“…A previous study had indicated that from 2010 to 2017, a total number of 1,506 SFTS cases and 7 humanto-human transmissions have been reported in Anhui Province (Gong et al, 2018). According to previous findings in Anhui Province, the economic burden was significantly high for patients with SFTS and their families, and effective preventive measures are necessary for endemic areas (Gong et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…And it is often at rest in winter, begins to increase in spring, and peaks by July-August, and the peak incidence rate of SFTS in Jiangsu Province has increased to some extent in recent years compared with 2011-2014. The R 2 and P values of the model fitting results for 2011 -2019 were listed in Table 3, and it can see that the model fitting results for all years were good and P was significant. (P < 0.05).…”
Section: Model Fittingmentioning
confidence: 99%
“…Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease infected by a novel bunyavirus, which is called Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV) [1]. The clinical manifestations of human infection have been characterized by high fever, a drastic reduction of platelets and leukocytes and hemorrhage [2,3,4,5]. The clinical course is mainly divided into three stages: fever, multiple nerve dysfunction and recovery [1,3,4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation